A chemical synthesis of a multiply 13C‐labeled hexasaccharide: a high‐mannose N‐glycan fragment. (8th July 2016) - Zhang, Wenhui; Pan, Qingfeng; Serianni, Anthony S.
Abstract : As covalent modifiers of proteins, high‐mannose N ‐glycans are important in maintaining protein structure and function in vivo . The conformations of these glycans can be studied by nuclear magnetic resonance spectroscopy using spin–spin couplings ( J ‐couplings; scalar couplings) and other nuclear magnetic resonance parameters that are sensitive to the geometries of their constituent glycosidic linkages and other mobile elements in their structures. These analyses often require 13 C‐labeling at specific carbon atoms, especially when measurements of 13 C‐ 13 C J ‐couplings are of interest. The selection of particular 13 C isotopomers of a glycan depends on the type of question under scrutiny. A chemical synthesis of a mannose‐containing hexasaccharide, α [1‐ 13 C]Man(1→2) α [1, 2‐ 13 C2 ]Man(1→6)[ α [1‐ 13 C]Man(1→2) α [1, 2‐ 13 C2 ]Man(1→3)] α [1, 2‐ 13 C2 ]Man(1→6) β ManOCH3, which is a nested fragment of the high‐mannose N ‐glycans of human glycoproteins and contains eight 13 C‐enriched carbon sites, is described in this report. The selected 13 C isotopomer was chosen to maximize the measurement of J ‐couplings sensitive to linkage conformations. This work demonstrates that chemical syntheses of multiply 13 C‐labeled oligosaccharides are technically feasible and practical using present synthetic methods. The availability of this and other multiply 13 C‐labeled mannose‐containing oligosaccharides will promote future studies of their conformations in solution and in the bound state. Abstract : A chemical synthesis of a mannose‐containing hexasaccharide, α [1‐ 13 C]Man(1→2) α [1, 2‐ 13 C2 ]Man(1→6)[ α [1‐ 13 C]Man(1→2) α [1, 2‐ 13 C2 ]Man(1→3)] α [1, 2‐ 13 C2 ]Man(1→6) β ManOCH3, which is a nested fragment of the high‐mannose N ‐glycans of human glycoproteins and contains eight 13 C‐enriched carbon sites, is described in this report. The selected 13 C isotopomer was chosen to maximize the measurement of J ‐couplings sensitive to linkage conformations. The availability of this and other multiply 13 C‐labeled mannose‐containing oligosaccharides will promote future studies of their conformations in solution and in the bound state.